Equilibrium and kinetic adsorption of drugs on bentonite: Presence of surface active agents effect - ÇALIŞKAN SALİHİ, ELİF (ELSEVIER, 2014)
The adsorption of five drugs: promethazine (PM), triflupromazine (TFP), trimethoprim (TM), carbamazepine (CM), and ibuprofen (IBU) onto bentonite (Bent) was studied spectrophotometrically in aqueous solutions and in the presence of different type of surfactants i.e. anionic sodium dodecyl sulfate (SDS) and cationic dodecyl trimethyl ammonium bromide (DTAB). The adsorption experiments were carried out as a function of time, initial concentration and temperature. Adsorption kinetic data were modeled using the Lagergren first order and the pseudo-second order kinetic equations. Interlayer diffusion graphics were also plotted. The data obtained from all kinetic studies are fitted to the pseudo-second order kinetic equation better than the Lagergren first order kinetic equation, except the adsorption of IBU onto Bent. The Giles isotherms were used to understand the adsorption mechanism of drugs. Isotherms plotted appear to fit L-type according to Giles isotherm classification. The Langmuir and Freundlich isotherms were used to model the equilibrium data obtained. The Langmuir model appears to fit the isotherm data better than the Freundlich model. The adsorption capacity values found for the adsorption of drugs in aqueous solutions followed the order: PM > TFP > TM > CM > IBU. It was observed that the presence of surfactants had significant effects on the adsorption capacities, although it did not affect the equilibrium time of the adsorption processes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Drug; Surfactant; Bentonite; Kinetics; Modification; CATIONIC SURFACTANT; AQUEOUS-SOLUTION; REMOVAL; WATER; PHARMACEUTICALS; HYDROCHLORIDE; PROMETHAZINE; TEMPERATURE; IBUPROFEN; GLASS